Ragam Bahasa Gaul dalam Caption Akun Instagram @Mimi.Peri - Maguna Eliastuti; Revi Aulia Safitri; Khulaefi Khulaefi; Desih Wulan Nugraha; Anita Theodore (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This research is trying to show the way slang words are formed and what they mean, especially abbreviations and acronyms. It also explains the different types of meanings slang can have. This study uses the same method. The information is in sentences and words on the Instagram page called @mimi.peri. The ways of collecting information are watching, noting, and keeping it in written records. This study discovered that the Instagram account @mimi.peri uses informal language in brief sentences. Slang words are often studied by people who research language. This research had 20 informal language examples. There are three different types of slang words. You can use three types of words: regular slang words, acronyms, and abbreviations.